A new species of Boletellus Section Chrysenteroidei (Boletaceae, Boletales) from southeast Yunnan, China - Zhang, Xin; Wu, Gang (Phytotaxa, 2022)
Species of Boletellus Section Chrysenteroidei are widely distributed in the world, especially in the subtropical to tropical regions. By means of molecular techniques, the species diversity of this section has become clearer and new taxa have been uncovered. In this study, a new species of this section from the southeast Yunnan of China, namely Boletellus wenshanensis, was identified based on molecular and morphological evidence. This species can be distinguised by the combination of morphological characters: a quick dark blue reaction on all parts of the basidiome when bruised, a brown to brownish orange pileus uncracking with age, a scaly stipe covered with brownish punctate squamules, yellow hymenophore, interwoven pileipellis, ellipsoid to broadly fusoid basidiospores ornamented with longitudinal ridges, and a hyphohymeniform stipitipellis. The new species is presented with illustrated description and comparisons with allied species.